Superconducting radiation detectors and their future perspectives - Kraus, H (1998)
Cryodetectors with superconducting sensors have been actively developed and optimized during the past years. This review discusses the operating principles of the two detector concepts, superconducting tunnel junctions and low-temperature bolometer or calorimeter. Progress in research with cryodetectors manifested itself by many successful device demonstrations and as a result, a shift in emphasis from pure detector optimization towards actual applications has been observed. Cryodetectors have been used for X-ray fluorescence, optical photon detection, mass spectroscopy of heavy molecules, etc. Nevertheless, there is still room for further improvement until the detectors will have actually reached their theoretical limitations.